A Postconviction Mentality: Prosecutorial Assistance in Exoneration Cases. (23rd February 2019) - Webster, Elizabeth
Abstract : Prosecutors' broad discretionary power has long been of interest to scholars, yet little is known about discretionary choices after conviction. This study addresses the gap by exploring prosecutors' willingness to assist with exonerations. Using data from the National Registry of Exonerations ( N  = 1, 610), the author identifies factors that influence prosecutorial assistance. Results from generalized ordered logistic regression models demonstrate that avoiding uncertainty and maintaining workgroup relationships drives decision-making. Findings indicate that prosecutors are less likely to support exonerations involving law enforcement or forensic misconduct, violent offenses, and inadequate legal defense and more likely to support exonerations involving innocence organizations, guilty pleas, and black and Hispanic defendants. These findings suggest that prosecutors' interest in protecting professional reputations, maintaining relationships, and optimizing efficiency influences discretion in the postconviction stage just as in earlier stages of case processing.